2015
DOI: 10.1111/ens.12145
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the diet of Tetrix tenuicornis (Orthoptera: Tetrigidae)

Abstract: Many animals change their diet during the season according to food availability. The current field study determined whether the groundhopper Tetrix tenuicornis (Orthoptera: Tetrigidae), which specializes on moss and detritus, changes its diet during the season under conditions in which food components are constantly available. Dietary differences of T. tenuicornis were studied through the season, from May to October, by alimentary tract analyses. Detritus and moss (phylloids) dominated the alimentary tract con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…As the diet of pygmy grasshoppers generally consists of algae, moss, fungi and lichen that thrive on wetter conditions (Paranjape et al 1987, Hochkirch et al 2000, Kočárek et al 2008, Bidau 2014, Kuřavová and Kočárek 2015, Kuřavová et al 2017a, our findings also suggested that greater abundance of food sources in wetter microhabitats can account for higher abundance of pygmy grasshoppers in general. We also found that specifically, the wetness of dicot leaf litter is strongly positively correlated with the abundance of pygmy grasshoppers.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As the diet of pygmy grasshoppers generally consists of algae, moss, fungi and lichen that thrive on wetter conditions (Paranjape et al 1987, Hochkirch et al 2000, Kočárek et al 2008, Bidau 2014, Kuřavová and Kočárek 2015, Kuřavová et al 2017a, our findings also suggested that greater abundance of food sources in wetter microhabitats can account for higher abundance of pygmy grasshoppers in general. We also found that specifically, the wetness of dicot leaf litter is strongly positively correlated with the abundance of pygmy grasshoppers.…”
Section: Discussionsupporting
confidence: 56%
“…Quantitative studies on the habitat/microhabitat association of pygmy grasshoppers are rare and restricted to a few species (e.g. Hochkirch et al 2000, Gröning et al 2007, Kuřavová and Kočárek 2015, Musiolek and Kočárek 2016, and even fewer in Southeast Asia. Southeast Asia consists of three biodiversity hotspots (Myers et al 2000), and is threatened by large-scale deforestation and land use conversion (Brooks et al 2002, Sodhi et al 2010, Wilcove et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…We omitted members of the Tetrigidae family, since these species are principally feeding on algae, lichens, mosses and detritus (e.g. Paranjape & Bhalerao ; Kuřavová & Kočárek ). We assumed that the measure of global grasshopper abundance is correlated with overall herbivore pressure on the plant community at each site.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous finding that behaviour is affected by barometric pressure caused us to hypothesize that groundhoppers might actively seek vegetation to avoid adverse weather consequences (Musiolek & Kočárek, ). European groundhoppers generally prefer wet semi‐vegetated habitats that also include patches without vegetation (bare ground), which is typically exploited for visual and vibrational communication (Hochkirch et al, ; Kočárek, ), and patches with mosses and detritus, which make up most of their diet (Kuřavová & Kočárek, ; Kuřavová, Grucmanová et al, ). Because individuals spend most of their time feeding (Lock and Durvael, ; Hochkirch et al, ), they are often found on these open patches.…”
Section: Discussionmentioning
confidence: 99%
“…Groundhoppers (Orthoptera: Tetrigidae) have been frequently used as models for ecological and behavioural studies (e.g. Forsman, ; Hochkirch, Gröning, & Krause, ; Kočárek, ; Karpestam, Wennersten, & Forsman, ; Kuřavová & Kočárek, , Kuřavová, Šipoš, Wahab, Kahar & Kočárek, ). Several species of groundhoppers typically occur in moist habitats including river banks and floodplains (Hochkirch et al, ; Kočárek, Holuša, Grucmanová, & Musiolek, ), where they are occasionally exposed to floods (Pushkar, ).…”
Section: Introductionmentioning
confidence: 99%